Meningkatkan Kinerja UKM Melalui Pendekatan Lima Kekuatan Porter - Dina Lusianti; Mutamimah Mutamimah; Mustika Widowati; Lela Zumala Rofiqoh; Mohammad Sapta Heriyawan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This community service program aims to enhance SMEs’ understanding and practical capacity in identifying, analyzing, and strengthening their strategic market positioning through Porter’s Five Forces framework. It enables business owners to assess competitive pressures from industry rivalry, new entrants, substitute products, and buyer bargaining power in developing sustainable business strategies. Methodology: The program was conducted through training, mentoring, and interactive discussions involving SME participants. The approach began with stakeholder mapping, followed by classification of business actors into competitors and partners, and finally the application of Porter’s Five Forces analysis Results: The results indicate that Small and Medium-Sized Enterprises (SMEs) were able to identify key stakeholders, distinguish between competitors and strategic partners, and understand their competitive position in the market. Participants showed improved strategic awareness in managing competition and collaboration. Conclusions: Porter’s Five Forces offers a practical, structured, and effective strategic framework that enables Small and Medium-Sized Enterprises (SMEs) to assess competitive dynamics, evaluate external market pressures, identify strategic opportunities and threats, and make more informed business decisions, ultimately improving overall business performance. Limitations: The program was limited to a small number of participants and short implementation duration. Contributions: This community service activity contributes to the development of Small and Medium-Sized Enterprises (SMEs) by systematically understand competitive market forces, improve strategic decision-making, strengthen market positioning, and enhance overall business performance to support sustainable business growth in an increasingly competitive environment.